Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd004009.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Intrarectal quinine for treating Plasmodium falciparum malaria

Abstract: We detected no difference in the effect on parasites and clinical illness for intrarectal quinine, but most trials were small. Pain may be less with intrarectal quinine. Further larger trials, in patients with severe malaria and in adults, are required before the intrarectal route can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These findings are particularly important, because there are limited data on the efficacy of intrarectal quinine for treatment of life-threatening forms of malaria. This study addresses a need for more trials, as recommended by Eisenhut et al [16].…”
Section: Discussionmentioning
confidence: 95%
“…These findings are particularly important, because there are limited data on the efficacy of intrarectal quinine for treatment of life-threatening forms of malaria. This study addresses a need for more trials, as recommended by Eisenhut et al [16].…”
Section: Discussionmentioning
confidence: 95%
“…A quarter of patients had liquid stools after first administration and when they reached the referral care centre the proportion increased to three quarters. In previous trials much lower proportion of liquid stools were reported [15,16]. Such difference can be explained by the differences in disease severity and clinical presentation at inclusion.…”
Section: Discussionmentioning
confidence: 91%
“…Provision of a wall chart indicating health education topics to be covered could also be an option to supplement the training. Several randomized trials indicate the clinical efficacy of rectal artesunate and rectal quinine is superior to the intravenous quinine in treatment of severe malaria [8][9][10]. Obviously, dosage routes other than the intravenous require less calculation skills and they might be considered as an alternative solution.…”
Section: Discussionmentioning
confidence: 99%